Pengawasan Internal dan Pelaksanaan Sistem Akuntansi Keuangan Daerah Serta Pengelolaan Keuangan Daerah terhadap Kinerja Pemerintah (Studi Kasus Pada Pemerintah Kabupaten Jepara 2017) - Subadriyah Subadriyah; Andre Anggriawan (Jurnal Rekognisi Akuntansi, 2017)
This research aims to test internal supervision conducted by the government, test the implementation of the Regional Accounting Financial System and test regional financial management that affects government performance in Jepara regency. This type of research is qualitative causal research. The population of this study is all OPD in Jepara Regency which amounted to 119 OPD. The sample was calculated with the Slovin technique so that 54 OPDs were obtained or about 54% of the total number of OPDs in Jepara Regency. The method of collecting data by conducting a survey directly spreads closed questionnaires. Data analysis method using multiple linear regression analysis The results showed that (a) internal supervision has a significant effect on Government Performance, (b) Implementation of Regional Financial Accounting System has a significant effect on Government Performance, (c) Regional Financial Management has a significant effect on Government Performance, and (e) simultaneous internal supervision, implementation of regional financial accounting system, regional financial management on government performance.